Re-thinking Adult Education Research. Beyond the Pandemic - Boffo, Vanna; Egetenmeyer, Regina (Studies on Adult Learning and Education, 2023)
This work is the result of the European INTALL Project, International and Comparative Studies for Students and Practitioners in Adult Education and Lifelong Learning (2018-2021). From early September 2018 to the end of August 2021, this project allowed us to build knowhow about some specific issues of adult education. The latest meeting of the INTALL project partners led to a conference about the role of Adult Education Research, during and after Covid-19, and the importance of re-thinking Lifelong and Lifewide Learning for the future. Based on four sections, Innovation and Future Competences in Adult Education Research, Professionalisation in Adult Education, Sustainability, Inclusion and Wellbeing: Topics for Adult Society and Smart Cities and Learning and Teaching in Higher Education in Post-Pandemic Time: A Digital Transformation, the volume represents an opportunity to foster a debate on key issues in the field of Adult Learning and Education across Europe.